Relation between division of household labor and attitudes toward gender roles with marital satisfaction in dual-earner families - Mihić, Vladimir; Filipović, Bojana (Primenjena psihologija, 2012)
The paper deals with the correlates of the marital satisfaction in the context of division of household labor. We examined differences in marital satisfaction depending on the division of household labor and attitudes toward gender roles. The sample consisted of 223 couples from dual-earner families. Marital satisfaction has been measured on a nine-point scale, while division of household labor has been determined by the Division of household labor scale consisted of three subscales-routine tasks, periodic tasks and tasks related to children. Attitudes toward gender roles has been measured by the ATGR scale designed in Croatia. The results show higher marital satisfaction in men, as well as traditional division of household labor (women do more routine tasks and tasks related to children, while men do more periodic tasks). However, attitudes toward gender roles tend to be more egalitarian than traditional, especially in women. Finally, marital satisfaction was significantly correlated with egalitarian attitudes and less routine work.